Mayo Clinic on Prostate Health - Barrett, David (Estados Unidos: Mayo Clinic Heallth, 1999)
Contiene información como llevar una buena salud y así evitar enfermedades futuras
CONTENIDO Chapter 1. About the prostate Chapter 2. Getting a prostate checkup Chapter 3. Living whith prostatitis Chapter 4. Understanding benign prostatic hyperplasia Chapter 5 treating beningn prostatic hyperplasia y otros ...
Incluye índice
Keywords: SALUD -- PREVENCIÓN; PROSTATA